Aptamer-functionalized nanomaterials for biological applications. (18th March 2020) - Ren, Qiaoli; Ga, Lu; Lu, Zhili; Ai, Jun; Wang, Tie
Abstract : This review comprehensively summarizes potential biological application using aptamer-functionalized nanomaterials platform, focusing on explaining syntheses, properties, prospects and challenges. Abstract : Aptamers have attracted the attention of many researchers because of their high stability, high affinity and high selectivity. Over the past decades, considerable intensive exploration and research has been carried out in this area. These studies have led to the emergence of functionalized nanomaterials, which have suggested a more diverse range of potential applications. However, despite the many exciting and remarkable developments emerging at the moment, several challenges and issues remain to be addressed. Based on currently reported aptamer-functionalized nanomaterials (AFNs), this review highlights potential applications for AFN platforms in catalysis, detection, cellular analysis, imaging, and targeted drug delivery. We also focus on explaining controllable syntheses and the unique dynamic properties of AFNs. Finally, we discuss progress and the challenges associated with AFN applications in this field.